Prevalensi dan Intensitas Ektoparasit Ikan Bawal Air Tawar (Colossoma macropomum) pada Usaha Perikanan Rakyat (UPR) di Desa Sepanjang, Kecamatan Glenmore, Banyuwangi - Yulianti, Indah Eka; Restu, I Wayan; Sari, Alfi Hermawati Waskita (Current Trends in Aquatic Science; Vol 2 No 1 (2019), 2019)
Freshwater Bawal fish (Colossoma macropomum) is one of the important fish species in freshwater cultivation activities. One of the qualities of good fish must be avoided from disease. Ectoparasites are parasites that attack the outside of the fish's body. This study aimed to determine the type, prevalence and intensity of freshwater Bawal fish ectoparasites (Colossoma macropomum) at UPR in Sepanjang village, Glenmore, Banyuwangi. Sampling of freshwater Bawal fish was taken using a purposive sampling method. The sample used was small fish (7.3-9 cm with a weight of 9.62 grams) and large fish (22.5-30.3 cm with a weight of 305.03 grams). 30 fish each. The data obtained were analyzed descriptively. The type of ectoparasites that infect small-sized freshwater Bawal fish include Trichodina sp. with a prevalence of 60% and intensity of 25 ind/fish, Ichthyophthirius multifiliis with a prevalence of 70% and intensity of 96 ind/fish, Dactylogyrus sp. with a prevalence of 100% and intensity of 23 ind/fish, and Gyrodactylus sp. with a prevalence of 23% and intensity of 2 ind/fish, whereas in large freshwater Bawal fish found ectoparasites such as Trichodina sp. with a prevalence of 10% and intensity of 2 ind/fish, Ichthyophthirius multifiliis with a prevalence of 90% and intensity of 66 ind/fish, Dactylogyrus sp. with a prevalence of 100% and intensity of 345 ind/fish, Gyrodactylus sp. with a prevalence of 23% and intensity of 11 ind/fish and the prevalence of Copepod 13% with an intensity of 1 ind/fish.